Prediction of social anxiety based on social support and social self-efficacy in adolescents with physical-motor disabilities - negar falamarzi; Diba Seif (Ravānshināsī-i Afrād-i Istis̠nāyī, 2020)
he purpose of this study was to predict social anxiety based on social support and social self-efficacy in physically-motorized disabled teens in Shiraz. Results showed that among the components of self-efficacy, self-efficacy for cognitive control (r = 0.41) and self-efficacy for control Emotional (r = -0.26) with a significant negative relationship with fear of negative evaluation. In addition, there was a significant relationship between social support components, emotional support / information (r = -0.24), and the support of kindness (r = -0.24) with general avoidance and distress. Among the components of social self-efficacy, self-efficacy for cognitive control (r = 0.32) and self-efficacy for emotional control (r = -0.36) is significantly correlated with avoidance and general grief. Also, there are no significant relationships between social support components with avoidance and distress in new situations. Also, among the components of self-efficacy, self-efficacy for cognitive control (r = 0.26) is significantly related to avoidance and grief in new situations. Regression results showed that among the components of social self-efficacy, only self-efficacy for cognitive control was significantly lowered by fear of negative evaluation (p <-0.401) and avoidance and general grief (p = 0.27) and anxiety and Predicts grief in new situations (p <0.01). Regarding the negative relationship between social support components and social anxiety, it is suggested that therapists and mental health professionals should pay more attention to the role of this variable in treatment interventions.